2004
DOI: 10.1002/nau.20054
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dopaminergic treatment on bladder function in Parkinson's disease

Abstract: The effects of dopaminergic treatment on bladder control and urodynamic parameters are unpredictable in the individual patient, though most patients experience significant changes. We have also demonstrated the complexity of bladder control, and that patients with PD may be particularly susceptible to develop complex micturitional dysfunction. Our data indicates that cortical dysfunction may play a significant role in bladder dysfunction in PD parallel to the pontine lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0
5

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 45 publications
2
62
0
5
Order By: Relevance
“…15 We have previously used this questionnaire in patients with PD. 3,8,16 The IPSS questionnaire consists of seven questions on LUTS and an additional question on general satisfaction of urinary conditions. Symptoms are scored on a frequency scale from 0 to 5.…”
Section: Questionnairesmentioning
confidence: 99%
See 2 more Smart Citations
“…15 We have previously used this questionnaire in patients with PD. 3,8,16 The IPSS questionnaire consists of seven questions on LUTS and an additional question on general satisfaction of urinary conditions. Symptoms are scored on a frequency scale from 0 to 5.…”
Section: Questionnairesmentioning
confidence: 99%
“…In the DanPSS, the total score is calculated as ⌺ 1-12 (symptom score ϫ bother score), thereby including bother of symptoms in the total assessment of LUTS. Questions in DanPSS are in three categories: (1) symptoms of obstructed voiding (questions 1-4 [DanPSS [1][2][3][4] ]), (2) symptoms of (neurogenic) overactive bladder or irritative symptoms (questions 5-8 [DanPSS [5][6][7][8] ]), 14 and (3) symptoms of pain, dripping, and stress incontinence (questions 9 -12).…”
Section: Questionnairesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is improved by chronic DRT with a D1-and D2-receptor-mediated increase in volume at which patients recognize bladder filling [Brusa et al 2007]. This effect of DRT is unclear and unpredictable in individual patients [Winge et al 2004]. STN-DBS has been shown to have variable results.…”
Section: Autonomic Dysfunctionmentioning
confidence: 99%
“…The unpredictable effect of medication is not related to stage of disease, age, or whether the patient had symptoms of bladder dysfunction (Winge et al, 2002). In the study of Winge and colleagues (Winge et al, 2004), the authors suggested that the effects of medication are mediated through cortical mechanisms, as the ability to separate and integrate sensory input measured using urodynamics is influenced by medication.…”
Section: The Pathophysiology Of Voiding Dysfunction In Parkinson's DImentioning
confidence: 99%